Complicated Carotid Artery Plaques and Risk of Recurrent Ischemic Stroke or TIA - Kopczak, Anna; Schindler, Andreas; Sepp, Dominik; Bayer-Karpinska, Anna; Malik, Rainer; Koch, Mia L; Zeller, Julia; Strecker, Christoph; Janowitz, Daniel; Wollenweber, Frank A; Hempel, Johann-Martin; Boeckh-Behrens, Tobias; et al. (Journal of the American College of Cardiology, 2022)
Complicated nonstenosing carotid artery plaques (CAPs) are an under-recognized cause of stroke. The purpose of this study was to determine whether complicated CAP ipsilateral to acute ischemic anterior circulation stroke (icCAP) are associated with recurrent ischemic stroke or transient ischemic attack (TIA). The CAPIAS (Carotid Plaque Imaging in Acute Stroke) multicenter study prospectively recruited patients with ischemic stroke restricted to the territory of a single carotid artery. Complicated (AHA-lesion type VI) CAP were defined by multisequence, contrast-enhanced carotid magnetic resonance imaging obtained within 10 days from stroke onset. Recurrent events were assessed after 3, 12, 24, and 36 months. The primary outcome was recurrent ischemic stroke or TIA. Among 196 patients enrolled, 104 patients had cryptogenic stroke and nonstenosing CAP. During a mean follow-up of 30 months, recurrent ischemic stroke or TIA occurred in 21 patients. Recurrent events were significantly more frequent in patients with icCAP than in patients without icCAP, both in the overall cohort (incidence rate [3-year interval]: 9.50 vs 3.61 per 100 patient-years; P = 0.025, log-rank test) and in patients with cryptogenic stroke (10.92 vs 1.82 per 100 patient-years; P = 0.003). The results were driven by ipsilateral events. A ruptured fibrous cap (HR: 4.91; 95% CI: 1.31-18.45; P = 0.018) and intraplaque hemorrhage (HR: 4.37; 95% CI: 1.20-15.97; P = 0.026) were associated with a significantly increased risk of recurrent events in patients with cryptogenic stroke. Complicated CAP ipsilateral to acute ischemic anterior circulation stroke are associated with an increased risk of recurrent ischemic stroke or TIA. Carotid plaque imaging identifies high-risk patients who might be suited for inclusion into future secondary prevention trials. (Carotid Plaque Imaging in Acute Stroke [CAPIAS]; NCT01284933).